1995
DOI: 10.1007/bf02536607
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of the enzyme glycerophosphodiesterase are present in human brain

Abstract: Brain levels of glycerophosphodiesters, including glycerophosphocholine (GPC) and glycerophosphoethanolamine (GPE), are altered in many human central nervous system disorders. Although much information is available on the enzymes responsible for the formation of these phospholipid metabolites, little information is known regarding their catabolism, by glycerophosphodiesterases, in human brain. In both autopsied and biopsied temporal cortex, a phosphocholine-producing glycerophosphodiesterase activity was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, GP-PDE enzymatic activity with GPC (GPC-PDE, EC 3.1.4.2), glycerophosphoethanolamine, or glycerophosphoinositol (glycerophosphoinositol PDE, EC 3.1.4.44) as substrates has been observed in a number of mammalian tissues including liver (25,26), brain (27), and kidney (28). Preliminary studies on the biochemical properties of the enzyme suggest that multiple enzymes may be responsible for the activity (29,30). The MIR16 protein identified in this study may represent one of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…However, GP-PDE enzymatic activity with GPC (GPC-PDE, EC 3.1.4.2), glycerophosphoethanolamine, or glycerophosphoinositol (glycerophosphoinositol PDE, EC 3.1.4.44) as substrates has been observed in a number of mammalian tissues including liver (25,26), brain (27), and kidney (28). Preliminary studies on the biochemical properties of the enzyme suggest that multiple enzymes may be responsible for the activity (29,30). The MIR16 protein identified in this study may represent one of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This was carried out as for choline kinase except that 100 µg of cytosolic protein was used, and ethanolamine replaced choline. Isolation of phosphoethanolamine was accomplished by modifying the procedure used for isolating phosphocholine (19), namely, the column was washed first with 2 mL of water, and phosphoethanolamine was eluted with 8 mL of water, as determined by comparision with a radiolabeled phosphoethanolamine standard. This procedure resulted in a recovery of approximately 60% for phosphoethanolamine, which was corrected for by running radiolabeled phosphoethanolamine standards in each assay.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 50 µg cytosolic or 80 µg of particulate protein was incubated for 1 h at 37°C in a buffer (final volume 50 µL) containing 15 mM magnesium chloride, 10 mM CTP, 1 mM 3 H-phosphoethanolamine (2 nCi/nmol), and 100 mM HEPES, pH 7.5, with alterations as described in the text. Following incubation, water-soluble products were extracted by the sequential addition of 200 µL chloroform/methanol [1:2 (vol/vol)], 50 µL chloroform, and 50 µL water (19). A 150 µL aliquot of the aqueous phase was dried by vacuum centrifugation, the residue resuspended in 30 µL of water containing 5 µg of ethanolamine, 10 µg of phosphoethanolamine, and 10 µg of CDPethanolamine, and applied to a silica gel TLC plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it is also possible that the toxicity of tellurite in demyelination may be ascribed to the inhibition of phosphocholine supply for re-synthesis of phosphatidylcholine [8,34]. There are at least two phosphodiesterases, which may supply phosphocholine in the resynthesis of phosphatidylcholine in brain tissue, as suggested from the previous publication that there might be two phosphodiesterases responsible for the conversion of GPC to phosphocholine in human brain samples [35]. From the present study, it is suggested that one enzyme may be GPC phosphocholine phosphodiesterase and the other, lysoPLC.…”
Section: Discussionmentioning
confidence: 91%